Mobilities in Socialist and Post-Socialist States
XIII, 263 p.
Keywords: This interdisciplinary collection explores what mobility meant, and still means, in the specific contexts of Soviet and East European socialist and post-socialist societies. Together the chapters consider diverse practices of mobility and their different contexts of power, resistance and inequality.